1963
DOI: 10.1139/v63-049
|View full text |Cite
|
Sign up to set email alerts
|

The Zinc Chloride Catalyzed Migration of Halogen in the Claisen Rearrangement

Abstract: The zinc chloride catalyzed rearrangement of allyl 2,6-dichlorophenyl ether in riitrobenzene solution gave a good yield of 2-allyl-4,6-dichlorophenol along with some 2,6-dichlorophenol and 2-methj 1-5,7-dichlorocoumaran. The coumaran increased a t the expense of the 2-allyl-4,6-dichlorophenol. This is in contrast to the therillal rearrangement of this ether, which gave mainly 4-allj I-2,6-dichlorophenol along with smaller amounts of 3-allyl-6-chlorophenol and 2-allyl-4,6-dichlorophenol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1963
1963
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In a recent publication (1) it was shown that the thermal Claisen rearrangement of allyl 2,6-dichlorophenyl ether gave not only the previously reported products, 4-allyl-2,6-dichlorophenol and 2-allyl-6-chlorophenol (2), but also a small yield (27,) of the halogen migration product, 2-allyl-4,6-dichlorophenol. The proportion of the halogen migration product increased to 7% and 11% respectively if the thermal rearrangement was conducted in nitrobenzene and in nitrobenzene containing lithium chloride.…”
Section: Introductionmentioning
confidence: 92%
“…In a recent publication (1) it was shown that the thermal Claisen rearrangement of allyl 2,6-dichlorophenyl ether gave not only the previously reported products, 4-allyl-2,6-dichlorophenol and 2-allyl-6-chlorophenol (2), but also a small yield (27,) of the halogen migration product, 2-allyl-4,6-dichlorophenol. The proportion of the halogen migration product increased to 7% and 11% respectively if the thermal rearrangement was conducted in nitrobenzene and in nitrobenzene containing lithium chloride.…”
Section: Introductionmentioning
confidence: 92%
“…band 2 (RF 0.36) gave 7-allyl-4-hydroxy-2-methyl-2,3-dihydrobenzofuran (4) (21).-A mixture of 4,6-diacetylresorcinol (1) (1.94 g, 10 mmol), N-bromosuccinimide (2.67 g, 15 mmol), and freshly distilled dioxane (25 ml) was refluxed for 10 h after which it was poured onto ice cold water (150 ml) with stirring. band 2 (RF 0.36) gave 7-allyl-4-hydroxy-2-methyl-2,3-dihydrobenzofuran (4) (21).-A mixture of 4,6-diacetylresorcinol (1) (1.94 g, 10 mmol), N-bromosuccinimide (2.67 g, 15 mmol), and freshly distilled dioxane (25 ml) was refluxed for 10 h after which it was poured onto ice cold water (150 ml) with stirring.…”
Section: Concentrationmentioning
confidence: 99%
“….-A mixture of compound (21) (1 g, 3.6 mmol), allyl bromide (1 ml, 10 mmol), and freshly ignited potassium carbonate (5 g) was refluxed in dry acetone for 24 h. Work-up as for compound (2) afforded a pale brown precipitate which on crystallisation from aqueous alcohol gave the title compound (23) as colourless prisms (730 mg (23) in N,N-Dimethylani1ine.-Compound (23) (700 mg, 1.9 mmol) was refluxed in N,N-dimethylaniline (5 ml) for 6 h after which workup of the mixture gave a dark red gum (650 mg). It showed 10 spots on a t.1.c.…”
Section: Preparation Of 5'-acetyl-2'4'-diallyloxy-3'-bromoacetophenonementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, protonation of the oxygen moieties by the sulfurous acid would promote prototropic rearrangement, conceivably as shown in Eq. (228). The stability of aminochromes is markedly dependent upon the pH of the solution.6".…”
mentioning
confidence: 99%